2013
DOI: 10.2214/ajr.12.9237
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Radiation Exposure of the Female Breast During Low-Dose Chest CT Using Organ-Based Tube Current Modulation and a Bismuth Shield: Comparison of Image Quality and Radiation Dose

Abstract: The radiation dose in the female breast may be reduced using a breast shield or organ-based tube current modulation during low-dose chest CT with acceptable image quality. The use of organ-based tube current modulation reduced the radiation dose in the breast without inducing image quality deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 16 publications
(27 reference statements)
3
35
0
5
Order By: Relevance
“…Generally, the bismuth shield application would lead to a beam hardening effect and starvation of information-carrying photons, resulting in an incorrect CT number being calculated during acquisition (Lee et al, 2011;Kim et al, 2013). The mean of the CT number and the SD of the CT numbers collected from the Setup A (no bismuth shield or bolus applied) can thus be used as the reference value of the CT number and image noise level in the present study.…”
Section: Resultsmentioning
confidence: 98%
“…Generally, the bismuth shield application would lead to a beam hardening effect and starvation of information-carrying photons, resulting in an incorrect CT number being calculated during acquisition (Lee et al, 2011;Kim et al, 2013). The mean of the CT number and the SD of the CT numbers collected from the Setup A (no bismuth shield or bolus applied) can thus be used as the reference value of the CT number and image noise level in the present study.…”
Section: Resultsmentioning
confidence: 98%
“…3 One study by Nikupaavo et al 6 used OBTCM on phantoms to reduce dose to the lens during head CT and reported 32% dose reductions. Similarly, Kim et al 34 reported dose reductions of 20.8% to the superficial breast tissue and 18.8% to the deep portion of the breasts, using OBTCM on female patients undergoing routine chest CT examinations.…”
Section: Organ-based Tube Current Modulationmentioning
confidence: 87%
“…5,19,33 Secondly, the breast is often incidentally exposed to large doses of radiation during CT procedures, even though they are rarely the area of interest. 34,35 Although routine chest CT scanning contributes to the majority of breast irradiation, numerous examinations are of concern. For example, CT pulmonary angiography can result in a mean glandular dose between 20-60 mGy, where as the inferior aspect of the breast can receive 10-20 mGy during abdominal CT. 5 Therefore because of the breasts overall projected radiosensitivity and high incidence of irradiation, reliable and practical dose reduction techniques must be routinely implemented.…”
Section: Breast Dose Reductionmentioning
confidence: 99%
See 2 more Smart Citations